Pengaruh Gaya Kepemimpinan, Motivasi Intrinsik dan Motivasi Ekstrinsik terhadap Produktivitas Kerja Karyawan Pada PT Tirta Sukses Perkasa Jember - Mohammad Yahya Arief; Umi Afifa (Valid: Jurnal Ilmiah, 2020)
The objectives studied are, are there variables of leadership style, intrinsic motivation and extrinsic motivation that have a partial, simultaneous and dominant influence on the work productivity variables of employees of PT. Tirta Sukses Perkasa Jember. The sampling technique in this study is to use saturated sampling technique with a total sample of 44 people. The analytical tool used is SPSS 22 for windows 7. Data collection was carried out by observation, interview, questionnaire and literature study methods. Data analysis methods used are multiple linear regression analysis, t-test, F test, dominant test, and the coefficient of determination. Leadership style, intrinsic motivation and extrinsic motivation have a positive effect on the Employee Productivity of PT. Tirta Sukses Perkasa, Jember Regency. Partially the leadership style influences Work Productivity. Leadership Style, Intrinsic Motivation and Extrinsic Motivation simultaneously influence and Intrinsic Motivation has a dominant effect on Employee Productivity at PT. Tirta Sukses Perkasa, Jember Regency